Hierarchical Modeling of Carbonate Fault-Controlled Paleokarst Systems: A Case Study of the Ordovician Reservoir in the Tahe Oilfield, Tarim Basin - Zhang, Wenbiao; He, Zhiliang; Duan, Taizhong; Li, Meng; Zhao, Huawei (Frontiers in Earth Science, 2022)
As a special type of fracture-cavity carbonate reservoir, fault/fracture-controlled paleokarsts are affected by large strike-slip faults with various storage spaces, irregular geometry, and stochastic spatial distribution, which brings new challenges to their 3D quantitative characterization and geological modeling. Based on multi-scale research data, a hierarchical scheme of a fault-controlled paleokarst is established for the Tahe oilfield, and then a hierarchical modeling method for the paleokarst is proposed based on the principles of hierarchical constraint and genetic control. The results show that the fault-controlled paleokarst hierarchy is divided into four levels according to genesis and scale. These are the strike-slip fault impact zone, the fault-controlled external paleokarst envelope, the fault-controlled internal paleokarst architecture, and the internal karst cave fillings. The strike-slip fault impact zone model is established using deterministic data of the main fault, secondary fault, envelope range, and key geological horizons obtained from seismic interpretation. Based on the seismic FL (Fault Likelihood) attribute, the external envelope model of the fault-controlled paleokarst is established using the deterministic method through automatic attribute segmentation and drilling calibration. With the constraint of the external envelope, the internal architectural elements are classified and modeled. A large-scale karst cave model and mesoscale discrete fracture distribution model are established using the deterministic method based on the seismic texture property and seismic ant property truncation. Taking well data as conditional data and seismic-geological probability cubes as constraint data, the sequential indication simulation and object-based marked point process simulation methods are used to obtain the model of the dissolution pores distribution and the model of the discrete small-scale fractures distribution, respectively. Finally, a typical fault-controlled paleokarst reservoir in the TP area of the Tahe oilfield is taken as an example to test the above modeling method; the 3D integrated model developed in this study can reflect the spatial hierarchy of the fault-controlled paleokarst carbonate reservoir.